Influence of self-esteem on the subjective happiness of female health officials from a primary health center in Chillan - Morales Ojeda, Ismael (2020)
Objective: To identify the relationship that self-esteem has on the subjective happiness of theemployees of the health area of a primary health center in Chillán. Methodology: Quantitativeapproach, non-experimental design, cross-sectional, and correlational type. the studied populationcorresponded to 250 civil servants analyzed in an intentional non-probabilistic sample of 105 people.The Rosemberg Self-Esteem Scale and the Lyubomirsky and Lepper Subjective Happiness Scalewere used as measurement instruments. Results: There is a relationship between the medians of thevariables average self-esteem and average subjective happiness, with a significance of (P <0.000) and a strength of R = 0.386. This evidenced a significant bilateral correlation between self-esteem andsubjective happiness, which showed that both variables influence each other. In addition, a relationshipwas found between economic income and self-esteem, where the higher-income group presented alower level of self-esteem. It was possible to visualize that the variables: age, income, marital status,education and religion do not have a significant relationship with subjective happiness. Conclusion:The possible reason for these results could be that well-being promotes positive emotions and a senseof individual worth that contributes to making life much more predictable and also acts as a bufferagainst stress by strengthening self-esteem.